I'm not your manic pixie dream girl - McNeil, Gretchen (Balzer + Bray, an imprint of HarperCollinsPublishers, 2016)
Beatrice Maria Estrella Giovannini is starting senior year at the top of her class, she's a shoo-in for a scholarship to M.I.T., and she's got a new boyfriend she's crazy about. But through high school Bea and her best friends Spencer and Gabe have been the targets of horrific bullying. So Bea uses her math skills to come up with a 100% mathematically guaranteed path to social happiness in high school. When her boyfriend Jesse dumps her for Toile, the quirky new girl at school, Bea reinvents herself as Trixie, a manic pixie dream girl in order to win Jesse back.